Framing Bias and Self-Control Bias in Retirement Savings Decision (Study on Educational Staff in Indonesia University of Education) - Fikri, Muhamad; Purnamasari, Imas (Universitas Pendidikan Indonesia, 2021)
The aim of this research is to prove how framing bias affects retirement savings decision and how self-control bias affects retirement savings decision in educational staff at the Indonesia University of Education. The research method used in this research is causal with a quantitative approach. This research used a questionnaire to collect primary data. Based on convenience sampling technique, respondents in this research are 296 employees from 34 units in the Indonesia University of Education. Statistical tools used in this research are McNemar’s test and logistic regression analysis. The conclusion of this research is framing bias affect retirement savings decision and self-control bias affect retirement savings decision negatively.